Strategi Pengumpulan Zakat Profesi Pegawai Negeri Sipil - Priyana, Yana (Universitas Nusa Putra, 2020)
This research is motivated by the lack of awareness of Civil Servants (PNS) to carry out the obligation to pay professional zakat, even after the BAZNAS conducted socialization to related agencies. The purpose of this research is to Analyze the Strategies of Collecting Professional Civil Servant Zakat in Amil Zakat Board in Sukabumi City. This research is based on field data using a descriptive qualitative approach. Data collected using observations, in-depth interviews, and documentation studies. This research found that there is a strategy used by BAZNAS in the management of professional zakat through socialization. Through socialization, BAZNAS immediately went to the field to visit the muzzaki candidates who were focused on civil servants (Civil Servants) through related agencies. As for the collection, the community comes directly to the BAZNAS office or can also be transferred to the BAZNAS account. In this study also found constraints faced by BAZNAS in carrying out management, especially professional zakat, namely the civil servants assume that civil servants' salaries do not meet Nishob, not calculated with benefits. After joining the basic wage with the allowance, the civil servant reaches Nishob to pay the zakat of the profession.